Selectively Biodegradable Polyesters: Nature-Inspired Construction Materials for Future Biomedical Applications - Urbánek, Tomáš; Jäger, Eliézer; Jäger, Alessandro; Hrubý, Martin (Polymers, 2019)
In the last half-century, the development of biodegradable polyesters for biomedical applications has advanced significantly. Biodegradable polyester materials containing external stimuli-sensitive linkages are favored in the development of therapeutic devices for pharmacological applications such as delivery vehicles for controlled/sustained drug release. These selectively biodegradable polyesters degrade after particular external stimulus (e.g., pH or redox potential change or the presence of certain enzymes). This review outlines the current development of biodegradable synthetic polyesters materials able to undergo hydrolytic or enzymatic degradation for various biomedical applications, including tissue engineering, temporary implants, wound healing and drug delivery.
Keywords: polycondensation; ring-opening; stimuli-sensitive; polyester; biodegradability; medical application; drug delivery